Elektrolit Padat Biobaterai Limbah Kulit Nanas dengan Penambahan NaOH dan Aki Bekas untuk Meningkatkan Tegangan dan Nilai Arus - Welly, Indah Sri; Fitrya, Neneng; Wirman, Shabri Putra; Dalimunthe, Latipa Hannum (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2024)
Indonesia produced a total of 3,203,775 tons of pineapples in 2022, generating approximately 4,024,800 kg of pineapple peel waste annually, which is then wasted. Therefore, this research aims to utilize pineapple peel waste as the main material for bio-batteries and employs Cu-Al electrodes. The objective of this study is to enhance the voltage and current of bio-batteries made from pineapple peel waste by maintaining the cells in a closed condition to reduce oxidation and using a denser electrolyte through the addition of NaOH and used battery electrolytes. This research employs an experimental method to determine the measurement values of voltage, current, power, light intensity, and bio-battery capacity. The research findings indicate that bio-batteries made from pineapple peel waste with the addition of NaOH and used battery electrolytes increase the maximum voltage and current by 181% and 100%, respectively, resulting in a power output of 36 mW and a light intensity of 540 lux. The best bio-battery capacity of 780 mAH is found in sample A3. Bio-batteries made from pineapple peel waste with the addition of NaOH and used battery electrolytes show potential as an alternative energy source.